Safety and efficacy of 26 compounds belonging to chemical group 3 (α, β‐unsaturated straight‐chain and branched‐chain aliphatic primary alcohols, aldehydes, acids and esters) when used as flavourings for all animal species and categories. (19th March 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of 26 compounds belonging to chemical group 3 (α, β‐unsaturated straight‐chain and branched‐chain aliphatic primary alcohols, aldehydes, acids and esters). They are all currently authorised as flavours in food. The FEEDAP Panel was unable to perform the assessment of non‐2( cis )‐en‐1‐ol [02.112] in the absence of data on its purity. The FEEDAP Panel concludes that hex‐2‐en‐1‐ol [02.020], pent‐2‐en‐1‐ol [02.050], 2‐dodecenal [05.037], nona‐2, 4‐dienal [05.071], trans ‐2‐nonenal [05.072], hex‐2( trans )‐enal [05.073], 2, 4‐decadienal [05.081], hepta‐2, 4‐dienal [05.084], deca‐2( trans ), 4( trans )‐dienal [05.140], dodec‐2( trans )‐enal [05.144], hept‐2( trans )‐enal [05.150], non‐2‐enal [05.171], undec‐2( trans )‐enal [05.184], trans ‐2‐octenal [05.190], trans ‐2‐decenal [05.191], tr ‐2, tr ‐4‐nonadienal [05.194], tr ‐2, tr ‐4‐undecadienal [05.196], hex‐2( trans )‐enyl acetate [09.394] and hex‐2‐enyl butyrate [09.396] are safe at the proposed maximum use level of 5 mg/kg feed for all animal species; nona‐2, 6‐dien‐1‐ol [02.049], trans ‐2, cis ‐6‐nonadien‐1‐ol [02.231], nona‐2( trans ), 6( cis )‐dienal [05.058], nona‐2( trans ), 6( trans )‐dienal [05.172], allyl heptanoate [09.097] and allyl hexanoate [09.244] are safe at the proposed normal use levels of 1 mg/kg complete feed for all animal species. No safety concern would arise for the consumer from the use of these compounds up to the highest safe levels in feed. In the absence of studies to assess the safety for the user, the FEEDAP Panel cannot conclude on the safety for the users when handling the additives. No environmental risk is foreseen for these compounds at the concentrations considered safe for the target species. Since the 25 compounds are used in food as flavourings and their function is essentially the same as that in food, no further demonstration of efficacy is necessary.